Cerebral folate deficiency: a neurometabolic syndrome? - Mangold, Sarah Jasmin Laureen; Blau, Nenad; Opladen, Thomas; Steinfeld, Robert; Weßling, Britta; Zerres, Klaus; Häusler, Martin (Molecular genetics and metabolism, 2011)
Background - Cerebral folate deficiency (CFD) is increasingly recognized in various neurological conditions, raising the question of whether it might represent a clear-cut clinical syndrome. - Methods - Retrospective analysis of patients with low cerebral spinal fluid (CSF) 5-methyltetrahydrofolate (5MTHF) values was performed. - Results - 58 pediatric patients with low (-2nd to -3rd standard deviation) and 45 patients with very low 5MTHF values (<3rd standard deviation) were identified, including 22 patients with defined underlying neurological conditions. The leading symptoms were mental retardation (n=84), motor retardation (n=75), epilepsy (n=53), ataxia (n=44) and pyramidal tract signs (n=37). There was no relationship between 5MTHF levels and the severity of clinical disease, the duration of clinical disease, distinct neurological symptoms and antiepileptic drug treatment, respectively. Genetical analysis for mutations in the folate receptor 1 gene proved normal in all 16 children studied. - Conclusions - For the majority of patients CFD is not a clear-cut neurometabolic syndrome but the common result of different genetic, metabolic or unknown processes. Nevertheless, CFD may represent a treatable disease-modifying factor which should therefore be addressed in prospective studies.
Gesehen am 09.08.2022